Ibero-American Studies - A. V. Shestopal; L. S. Okuneva (Vestnik MGIMO-Universiteta)
Traditions of the Ibero-American Studies at MGIMO were laid by generation of professors who taught at the MGIMO University in the late 1940s - early 1950s. Among them were such distinguished scholars as historian L.I. Clove and economic geographer I.A. Witwer. The formation of the first generation of iberoamerican scholars at MGIMO took place in an atmosphere marked by fresh memories of the Spanish Civil War and the convergence of the USSR and the countries of Latin America, with the majority of which diplomatic relations were established. The outbreak of the "cold war" reduced to a minimum soviet relations with the Spanish-speaking countries. The creative potential of students of Zubok and Witwer was fully revealed only in 1960-1970-ies. when the historical fate of Russia and Latin America once again converged and intertwined. A number of graduates students of Ibero-American studies (U.V. Dubinin, M.F. Kudachkin, N. Leonov, K.A. Hachaturov, G.E. Hatters) in those years successfully combined practical and scientific activities. MGIMO graduates have contributed greatly to the establishment of the leading centers of domestic Latin American studies - Institute of Latin America and the journal "Latin America."